MIN 8 Aceh Barat Daya لترقية قدرة التلاميذ على مهارة الكتابة بـــ (Projector) الإملاء المنظور بوسيلة كشاف ضوئي - Rafid, Sulthan; Hamdiah, Hamdiah; Fadhilah, Fadhilah (لســـانـنــا (LISANUNA): Jurnal Ilmu Bahasa Arab dan Pembelajarannya, 2023)
The purpose of this research is to find out the application of imlak manzur using projector media can improve students' writing skills. The research method used by the researcher is experimental research. To collect data, researchers conducted pre-test, post-test. The research population is all students at MIN 8 Aceh Barat Daya while the sample in this study is grade 5 students, totaling 30 students. The research results obtained in this thesis, namely the results of the paired sample T-test -18.660 (sig<0.05) and the results of the independent sample T-test 0.489 (sig>0.05) at the significance level (Sig) (0.05> 0.00) and this shows that the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted.